THE INFLUENCE OF FINANCIAL MANAGEMENT ON THE TURNOVER OF MICRO SMALL AND MEDIUM ENTERPRISES (UMKM) - Deanova, Akbar; Simamora, Tongam; Satria, Widi Dwi (Universitas Negeri Yogyakarta, 2024)
Effective financial management is crucial for the sustainability of businesses, including micro, small, and medium enterprises (MSMEs). Sound financial management practices can significantly impact the turnover and overall performance of MSMEs. This abstract aims to examine the influence of financial management on the turnover of MSMEs and underscore the importance of sound financial practices for their growth and development. This study adopts a quantitative approach using an Ex Post Facto research design. Data collection is conducted through questionnaires. The pilot test results, administered to a sample of respondents, validate the usability of the instrument for data collection. The research sample comprises MSME owners, selected through random sampling. Prerequisite tests, including normality testing and linearity testing, are conducted. Data analysis employs the Pearson product-moment correlation technique and simple linear regression analysis. The findings reveal a significant relationship between financial management and the turnover of MSMEs, as evidenced by the correlation coefficient. The results indicate a strong correlation between financial management and turnover. The regression analysis demonstrates the percentage of influence of financial management on business turnover. The regression model is found to be suitable for predicting the business turnover variable. Therefore, it can be concluded that financial management significantly influences the turnover of MSMEs..